Eksistensi Tuhan Menurut Immanuel Kant: Jalan Moral Menuju Tuhan - L. Tjahjadi, Simon Petrus (Jurnal Orientasi Baru, 2009)
What is the relation between ethics, happiness and â€Godâ€? Immanuel Kant hasa web of arguments explaining their intertwined relations in his well knownworks. This body of arguments laid an intellectual bridge between philosophyand theology. God is understood as 1) a moral unit who ensures the absoluteautonomy of human conscience, as well as 2) guarantee the foundation ofmorality or the ultimate meaning of morality. Yet, this kind of â€Godâ€ isnamed by Kant as â€postulateâ€, meaning that the existence is to be acceptedunconditionally or needless to prove it otherwise. In Fakta der Vernunft, KpV,A 289, Kant named it as â€the fact of reasonâ€. This means that for humanbeings, ethics, happiness and God are to be accepted beyond any doubt (asin the case of a fact). On the other hand, they should not be considered asan empirical constancy, as to be able to be finger-pointed, however as a resultof a conclusion of a work of human practical reason along with his or hermoral effort.